Blood Coagulation and Acid-Base Balance at Craniocerebral Hypothermia in Patients with Severe Traumatic Brain Injury - V. E. Avakov; I. A. Shakhova (Общая реаниматология, 2015)
Systemic therapeutic hypothermia has gained a negative reputation in treating multiple trauma patients and is regarded as one of the factors in the lethal triad of shock, acidosis, and hypothermia. This fact owes to no relationship between acidosis and hypothermia; the effects of the latter on coagulation are evident and complexly reversible in the presence of acidosis.Objective: to determine the impact of noninvasive local brain cooling on the metabolic and blood coagulation indicators of a patient with acute cerebral ischemia.Subjects and methods. The subjects of the study were 113 patients with severe brain injury, including that complicated by the involvement of stem structures, who underwent brain cooling in different modifications. In so doing, the val ues of acidbase balance and coagulation system in arterial and venous blood were investigated.Results. Local brain hypother mia was not found to affect coagulation while the baseline negative values of excess buffer bases showed positive values (a right shift) by the end of cooling. Recommendations were given to prevent metabolic shifts.Conclusion. Patients at very high risk for bleeding may be safely cooled to a brain temperature of 32—34°C even in the presence of moderatetosevere acidosis. This is a great advantage of local hypothermia over systemic one.